2012
DOI: 10.1111/j.1540-5915.2011.00336.x
|View full text |Cite
|
Sign up to set email alerts
|

Co‐Op Advertising in Dynamic Retail Oligopolies

Abstract: We study a supply chain in which a consumer goods manufacturer sells its product through a retailer. The retailer undertakes promotional expenditures, such as advertising, to increase sales and to compete against other retailer(s). The manufacturer supports the retailer's promotional expenditure through a cooperative advertising program by reimbursing a portion (called the subsidy rate) of the retailer's promotional expenditure.To determine the subsidy rate, we formulate a Stackelberg differential game between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(20 citation statements)
references
References 40 publications
0
20
0
Order By: Relevance
“…There are some cooperative advertising works that focus on a "multiple-retailer" framework. For example, He et al [28,29] extended He et al [19] by considering the competing retailers, and their results showed that the manufacturer's support for its retailer is higher under competition than in its absence.…”
Section: Literature Reviewmentioning
confidence: 98%
“…There are some cooperative advertising works that focus on a "multiple-retailer" framework. For example, He et al [28,29] extended He et al [19] by considering the competing retailers, and their results showed that the manufacturer's support for its retailer is higher under competition than in its absence.…”
Section: Literature Reviewmentioning
confidence: 98%
“…Empirical data clearly show an increasing trend, e.g., from $15 billion which were spent for such programs in the United States of America in 2000 up to $50 billion in 2008 (cf. He et al 2012;Nagler 2006). However, Nagler's study reveals that manufacturers mostly set their participation rates to 50 % or 100 % instead of conducting an appropriate analysis on the optimum percentage.…”
Section: Introductionmentioning
confidence: 91%
“…Some scholars studied on cooperative advertising present dynamic models and differential games for long-term, multiperiod relationships between manufacturers and retailers (e.g., see [12][13][14]). Others focus on a static, single-period relationship involving cooperative advertising (e.g., see [15][16][17][18]).…”
Section: Introductionmentioning
confidence: 99%